Wheat: Grain Structure of Wheat and Wheat-based Products - Solah, Vicky; Fenton, Haelee; Crosbie, G. (2015)
© 2016 Elsevier Ltd. All rights reserved. The world's population relies on wheat-based foods as a major source of essential energy. Wheat-based foods are a good source of nutrients such as carbohydrates, proteins, and fiber for humans, but most food applications use milled wheat as white or purified flour and some valuable nutritional components may be lost. While carbohydrates should be the body's major source of energy, diets rich in whole grain are recommended for the prevention of cardiovascular disease. This protective aspect of whole grain and the importance of whole grain food must be highlighted to ensure they form a significant part of the diet. The composition, structure, and special properties of the wheat grain have allowed the evolution of many unique food products worldwide.